PERILAKU MENGGANGGU DI KELAS - Taufiq Hendra Wicaksono (Paradigma, 2013)
Characteristics and indicators of disruptive behavior and there is no common characteristic at each age level school (playgroup, kindergarten, elementary, junior high, high school or university). Disruptive behavior can be divided into three levels, namely mild, moderate and severe. The reasons for this can come from internal or external actors. Handling problems and disruptive behavior can be observed from behavioristik approaches, cognitive and humanistic. Through this article classroom teachers and teacher guidance and counseling are expected to understand and handle disruptive behavior so as to maximize the teaching and learning process in the classroom.